Apocrine metaplasia: a new type of müllerian metaplasia. Issue 6 (June 1993) - Allen, C; Johnson, S
Abstract : Apocrine differentiation was an incidental finding in an ovarian cyst. This is considered to be a further example of Müllerian metaplasia that has not been described before and which, theoretically, could occur in any organ of Müllerian derivation (ovary, uterus, cervix or fallopian tube). It is suggested that sites of such metaplasia could in turn be the origin of primary apocrine carcinoma in any of the above locations.